TED Talks: An Influential Medium to Improve Students’ Listening Skill - Ramadhan, Rifqi; Aminatun, Dyah (Jurnal Riset dan Inovasi Pembelajaran, 2024)
Listening difficulties in English often stem from a lack of confidence and issues with concentration, particularly noticeable among students at SMAN 1 Pringsewu, who often feel anxious and unsure when communicating in English class. To tackle this challenge, a learning approach that enhances focus and confidence is crucial. Researchers have opted for TED Talks as a solution. These talks offer concise yet profound ideas within a span of 18 minutes, presenting engaging and informative content that can bolster listening skills. Employing quantitative research methods with a quasi-experimental design, researchers collected data from students' pre-test and post-test scores. The findings indicate that TED Talks effectively assist students, sparking their interest and enthusiasm for English studies. Consequently, the researchers posit that when students have the opportunity to listen at their own pace, they exhibit improved concentration in listening and are mentally better equipped for learning.